Application of Conversation Exercises in Patients with Auditory Hallucinations - Septirina, Septirina; Reni, Reni; Listi, Listi (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
Mental disorders can be suffered by anyone. Mental patients are seen by society as someone who is stupid, strange and dangerous. Mental disorders that are one of the main problems in developing countries are schizophrenia. Schizophrenia is a condition characterized by severe mental disorders such as hallucinations, delusions that can affect the thoughts, feelings and behavior of individuals, loss of understanding of reality and loss of self-awareness. The prevalence of schizophrenia in Indonesia is 6.7% with a distribution area in urban areas of 6.4% and rural areas of 7.0%, while the coverage of treatment for schizophrenia is 85.0%. The research method uses a descriptive case study approach which aims to create descriptions, pictures, and paintings systematically. This study applies conversation exercises to patients with auditory hallucinations through exercises that focus patients on conversation and prevent patients from interacting with their hallucinations. Auditory hallucinations can be overcome by rebuking hallucinations, talking to other people or people closest to them. The results of this study indicate that talking to other people is effective in stopping hallucinations because it keeps patients busy doing activities of talking to other people